2020
DOI: 10.1002/adma.201908521
|View full text |Cite
|
Sign up to set email alerts
|

Stable Rhodium (IV) Oxide for Alkaline Hydrogen Evolution Reaction

Abstract: Water electrolysis in alkaline electrolyte is an attractive way toward clean hydrogen energy via the hydrogen evolution reaction (HER), whereas the sluggish water dissociation impedes the following hydrogen evolution. Noble metal oxides possess promising capability for catalyzing water dissociation and hydrogen evolution; however, they are never utilized for the HER due to the instability under the reductive potential. Here it is shown that compressive strain can stabilize RhO2 clusters and promote their catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 27 publications
2
83
0
1
Order By: Relevance
“…The HER catalytic activity of the as-synthesized samples in alkaline solutions was also assessed. [27,28] Remarkably, to reach a current density of 10 mA cm À 2 , CoFeP@Ru exhibits a low overpotential of only 48 mV in 1.0 M KOH, much lower than that CoP@Ru (194 mV) (Figure 3d), comparable to most Ru-based HER electrocatalysts reported previously (Table S3). Meanwhile, the Tafel slope of CoFeP@Ru is 41 mV dec À 1 , smaller than that of Pt/C (39 mV dec À 1 ) and CoP@Ru (116 mV dec À 1 ) (Figure 3e).…”
Section: Resultssupporting
confidence: 59%
“…The HER catalytic activity of the as-synthesized samples in alkaline solutions was also assessed. [27,28] Remarkably, to reach a current density of 10 mA cm À 2 , CoFeP@Ru exhibits a low overpotential of only 48 mV in 1.0 M KOH, much lower than that CoP@Ru (194 mV) (Figure 3d), comparable to most Ru-based HER electrocatalysts reported previously (Table S3). Meanwhile, the Tafel slope of CoFeP@Ru is 41 mV dec À 1 , smaller than that of Pt/C (39 mV dec À 1 ) and CoP@Ru (116 mV dec À 1 ) (Figure 3e).…”
Section: Resultssupporting
confidence: 59%
“…by surface structure engineering, as good HER catalytic materials. [138][139][140][141] This undoubtedly indicates the potential of metal oxides in the field of electrocatalysis. At the same time, it is also possible to combine CeO 2 with metal oxides to further modulate the surface, interface structure and generate excellent hybrid catalysts for HER.…”
Section: Ceo /Metal Oxide Composite Catalysts For Hermentioning
confidence: 94%
“…Liang et al [ 110 ] prepared Au-ZnO nanospheres with Au NPs in different particle size encapsulated in ZnO nanospheres through laser irradiation of the Au target and Zn target in liquid, respectively. Otherwise, Liu and Du et al reported the synthesis of RuAu single-atom alloys (SAAs) [ 111 ] and RhO 2 clusters embedded in the surface of Rh nanoparticles [ 112 ] by PLAL technique, the strong quenching effect played an important role in fabricating metastable nanostructures with novel properties (Fig. 8 a).…”
Section: Laser As the Synthetic Techniquementioning
confidence: 99%